Does curcumin administered in the early post weaning period have long lasting beneficial effects in rats on a high fructose diet? - Goba, Lihle Ayanda (My University, 2020)
Increased intake of fructose is associated with metabolic disorders such as obesity and other obesity-related complications. These metabolic disorders also affect children and it is essential to find strategies to prevent the adverse effects. The early post weaning period is a window of developmental plasticity which can be targeted for long lasting beneficial health effects. The use of phytomedicines has increased as they are inexpensive, safe and potentially have positive metabolic health benefits. This study investigated the potential of a phytomedicine, curcumin, in the early post weaning phase to induce long term positive metabolic health benefits in male and female rats on a high fructose diet. Eighty, 21 - day old rat pups (n = 40 males and n = 40 females) were randomly allocated into five treatment groups (n = 8 males and n = 8 females per group); Group I was fed standard rat chow (SRC), plain drinking water (PDW) and plain gelatine cubes (PGC), II was fed SRC, 20% FS as drinking fluid and PGC from postnatal day 21 to 35 and then SRC and 20 % FS for the rest of the study, III was fed SRC, 20% FS and curcumin (500mg/kg body weight) in gelatine cubes (GC) from postnatal day 21 to day 35 and then SRC and 20% FS, IV was fed SRC, PDW and curcumin at 500mg/kg body weight in GC from postnatal day 21 to 35 and then SRC and PDW, while V was fed SRC, PDW and fenofibrate (100mg/kg body weight) in GC from postnatal day 21 to 35 and then SRC and 20% FS for the remainder of the study. Male rats fed fructose and curcumin were significantly (p<0.05) lower in body mass compared to the controls. The body mass of female rats showed no significant differences across treatment groups. No significant differences (P>0.05, ANOVA) were observed in the triaglycerol and cholesterol concentrations as well as the insulin and adiponectin concentrations between groups. In the visceral organs of the males, the fructose fed rats had smaller small intestines compared to controls, as well as lower absolute large intestine masses and relative stomach masses (P<0.05). In the male rats fed fructose, a microsteatosis score of 1 was observed. In the female rats fed curcumin and fenofibrate alone, a microsteatosis score of 1 was observed. In male and female rats fed fructose alone, a score of 1 for microsteatosis and 0 for macrosteatosis was observed. The negative effects of fructose in the liver were attenuated by curcumin. Thus, strategic administration of curcumin during the early postweaning period should be further explored for the prophylaxis of diet induced NAFLD.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020